2020
DOI: 10.1111/jon.12818
|View full text |Cite
|
Sign up to set email alerts
|

Venous Diameter Changes in Chronic Active Multiple Sclerosis Lesions

Abstract: BACKGROUND AND PURPOSE: To investigate the temporal evolution of venous diameter in chronic active and nonenhancing shrinking multiple sclerosis (MS) lesions in a longitudinal magnetic resonance imaging (MRI) study including susceptibilityweighted images (SWI). METHODS: We compared the venous diameter in chronic active and nonenhancing shrinking lesions to the venous diameter in nonenhancing stable lesions on two 3 T MRI data sets obtained 12 months apart. Chronic active and nonenhancing shrinking lesions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Recently, there has been an increasing interest in "chronic active" MS lesions that are associated with higher disease severity and ongoing tissue destruction as an imaging biomarker of disease progression [3][4][5][6][7][8]. Histopathologically, chronic active lesions are characterised by a self-sustained low degree of chronic inflammation, active myelin breakdown, neurodegeneration, axonal loss, and progressive tissue matrix damage driven by a rim of iron-laden activated microglia/macrophages and reactive astrocytes at the lesion edge [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been an increasing interest in "chronic active" MS lesions that are associated with higher disease severity and ongoing tissue destruction as an imaging biomarker of disease progression [3][4][5][6][7][8]. Histopathologically, chronic active lesions are characterised by a self-sustained low degree of chronic inflammation, active myelin breakdown, neurodegeneration, axonal loss, and progressive tissue matrix damage driven by a rim of iron-laden activated microglia/macrophages and reactive astrocytes at the lesion edge [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…In a pathological survey on 2476 WMLs in MS, expanding lesions were predominantly found in progressive MS and were suggested to indicate progressive disease activity [20]. On the other hand, lesion shrinkage might be related to tissue repair and reduced inflammatory activity with the resolution of extracellular water as part of inflammatory edema [21]. Having lesions with IRLs would be associated with the active disease process and severity.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that DMV scores decreased as hemoglobin levels increased, implying better continuity of DMVs. SWI is a blood‐oxygen‐dependent MR sequence that is sensitive to iron in the form of hemosiderin and deoxyhemoglobin (Weber et al., 2021). Through oxygen metabolism in brain tissue, hemoglobin in the blood is converted into deoxyhemoglobin.…”
Section: Discussionmentioning
confidence: 99%